Group photograph of staff at nylon plant in Martinsville, Virginia (1950)
Group photograph of staff from DuPont's nylon plant in Martinsville, Virginia. Supervisor C.P. White is visible in the front row, far left side. The rest of the individuals depicted in the photograph are unidentified.
Keywords: Employees; Nylon; E.I. du Pont de Nemours & Company; Women employees; Portraits, Group